Development and Characterization of Dual-Loaded Niosomal Ion-Sensitive In Situ Gel for Ocular Delivery - Viliana Gugleva; Rositsa Mihaylova; Katya Kamenova; Dimitrina Zheleva-Dimitrova; Denitsa Stefanova; Virginia Tzankova; Maya Margaritova Zaharieva; Hristo Najdenski; Aleksander Forys; Barbara Trzebicka; Petar D. Petrov; Denitsa Momekova (Gels)
The study investigates the development and characterization of dual-loaded niosomes incorporated into ion-sensitive in situ gel as a potential drug delivery platform for ophthalmic application. Cannabidiol (CBD) and epigallocatechin-3-gallate (EGCG) simultaneously loaded niosomes were prepared via the thin film hydration (TFH) method followed by pulsatile sonication and were subjected to comprehensive physicochemical evaluation. The optimal composition was included in a gellan gum-based in situ gel, and the antimicrobial activity, in vitro toxicity in a suitable corneal epithelial model (HaCaT cell line), and antioxidant potential of the hybrid system were further assessed. Dual-loaded niosomes based on Span 60, Tween 60, and cholesterol (3.5:3.5:3 mol/mol) were characterized by appropriate size (250 nm), high entrapment efficiency values for both compounds (85% for CBD and 50% for EGCG) and sustained release profiles. The developed hybrid in situ gel exhibited suitable rheological characteristics to enhance the residence time on the ocular surface. The conducted microbiological studies reveal superior inhibition of methicillin-resistant Staphylococcus aureus (MRSA) adhesion by means of the niosomal in situ gel compared to the blank gel and untreated control. Regarding the antioxidant potential, the dual loading of CBD and EGCG in niosomes enhances their protective properties, and the inclusion of niosomes in gel form preserves these effects. The obtained outcomes indicate the developed niosomal in situ gel as a promising drug delivery platform in ophthalmology.